Haldane's rule in the placenta: Sex‐biased misregulation of the Kcnq1 imprinting cluster in hybrid mice. (1st December 2020) - Arévalo, Lena; Gardner, Sarah; Campbell, Polly
Abstract: Hybrid phenotypes that contribute to postzygotic reproductive isolation often exhibit pronounced asymmetry, both between reciprocal crosses and between the sexes in accordance with Haldane's rule. Inviability in mammalian hybrids is associated with parent‐of‐origin placental growth abnormalities for which misregulation of imprinted gene (IGs) is the leading candidate mechanism. However, direct evidence for the involvement of IGs in hybrid growth dysplasia is limited. We used transcriptome and reduced representation bisulfite sequencing to conduct the first genome‐scale assessment of the contribution of IGs to parent‐of‐origin placental growth dysplasia in the cross between the house mouse ( Mus musculus domesticus ) and the Algerian mouse ( Mus spretus ). IGs with transgressive expression and methylation were concentrated in the Kcnq1 cluster, which contains causal genes for prenatal growth abnormalities in mice and humans. Hypermethylation of the cluster's imprinting control region, and consequent misexpression of the genes Phlda2 and Ascl2, is a strong candidate mechanism for transgressive placental undergrowth. Transgressive placental and gene regulatory phenotypes, including expression and methylation in the Kcnq1 cluster, were more extreme in hybrid males. Although consistent with Haldane's rule, male‐biased defects are unexpected in rodent placenta because the X‐chromosome is effectively hemizygous in both sexes. In search of an explanation, we found evidence of leaky imprinted (paternal) X‐chromosome inactivation in hybrid female placenta, an epigenetic disturbance that may buffer females from the effects of X‐linked incompatibilities to which males are fully exposed. Sex differences in chromatin structure on the X and sex‐biased maternal effects are nonmutually exclusive alternative explanations for adherence to Haldane's rule in hybrid placenta. The results of this study contribute to understanding the genetic basis of hybrid inviability in mammals, and the role of IGs in speciation.